(3Ndb GdEfSGfs - (3KGHJ Hf CHj KGHJ SYjO Gdchaj , CHh eMeO,J (B250 (3g` s
(3ChdgG (B:s
(3Gi de JMed hdOkG hjbGd (B: (3hVYJ adGfI Yf adGfI JbQFgG JbQjFkG (B: (3Ci Jchf YfOgG MJi JfbVi YOJgG hJMjV KdGKkG hgPG cKjQ fcQI Cf JWhd Hg GdcJGH s
(3BNQgG (B:s
(3hCfTO GdCUeYfi dHYV GdQLGR NRYdI GdVHYGf QGM GdgfHdI aEPG eQ jVWQH ai Ndbg cdg eSJQNjkG ai eTjg , bjd (B: (3eQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3ChdgG eHJhQ hGdfGbU efgG fMh hQbJjfs
(3BNQgG eHJhQ PgH efgG hQbI hGMOI hSbW ef OGNdgG TF bdjds
(3fSNI QGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B97 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B100 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B248s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
Keywords: (3GddZIs